Sam Houston, Hero of San Jacinto - Gonzalez, Catherine Troxell (Austin, TX : Eakin Press, 1983)
Tells the story of the life of the frontier hero and statesman of Texas.
Keywords: Houston, Sam, 1793-1863; Houston, Sam, 1793-1863; Texas -- History; Texas -- History